Presentations in english : - Williams, Erica J. (Macmillan, 2008)
This book for my college English majors in Korea. Several weeks into it the book I am deeply regretting my choice. The material is incredibly boring and difficult. Even then, I wouldn't recommend this book even to advanced students of English. The presentations on the DVD are unnecessarily technical and often spoken in accents that few will be able to decipher. There are some online teachers' materials, but they're hardly helpful. I wish I'd spent another couple hours previewing this book before I committed to it!